The Development Of E-Mathematics Modules As Alternative Teaching Materials For Students On Material Of Set At SMP Muhammadiyah 8 Medan - Rona Nur Pasiuli Harahap (UMSU, 2022)
This type of research uses Research and Development (RD) development. This development research was conducted to produce a product and determine the validity, student responses to the E-module as an alternative student teaching material that has been produced. This product was developed using the ADDIE model which was modified into 3 stages, namely analysis, design, and development. This study developed the E Mathematics module as an alternative teaching material for students on set material at SMP Muhammadiyah 8 Medan. The subjects of this study were students of class VII junior high school which consisted of 10 students, where the researcher selected respondents based on a small scale. E the module that has been created meets the criteria of validity shown by using the validation sheet of media experts and material experts. The results of the media expert's validation reached an average score of 3.06 with the criteria, and the results of the material expert's validation reached an average score of 3.15 with valid criteria. The attractiveness aspect based on student responses reached an average score of 3.43 in the interesting category. Based on the results of research and discussions that have been carried out, it can be said that the e-mathematics module as an alternative teaching material on set material is feasible and interesting to use in terms of aspects of validity and student responses.